Impact of education on cerebral cortex volume, thickness and Alzheimer’s disease - Biskupski, Maciej; Bartoszczyk, Martyna; Ostański, Jan; Daniluk, Aleksander; Iwaniuk, Kaja; Buczek, Jakub; Białkowska, Zuzanna; Samczuk, Maciej; Stachowicz, Hubert; Olszak, Joanna (Quality in Sport, 2024)
Introduction and objective: The purpose of our review was to systematize the knowledge regarding the impact of education on cortical volume and thickness along with assessment of the risk and progress of Alzheimer’s disease. We considered the problem among children as well as adults, depending on their level of education and particularized the role of cognitive reserve as a protection from brain damage. Furthermore, we investigate the issue of neuronal tolerance in Alzheimer’s disease. Review methods: The article is a review of 22 original papers, cohort studies and meta-analyses concerning the impact of education on cortical volume and thickness along with the risk and progress of Alzheimer’s disease. Abbreviated description of the state of knowledge: Studies have shown that education is associated with an increase in intelligence, which determines the dynamics of brain cortex changes among children. In adults, the thickness of individual brain areas - primarily the temporal and frontal poles - enhances with the increase of their education level. The dynamics of changes in cortical measurements are correlated with education both in healthy adults and in patients with Alzheimer’s disease. A healthy lifestyle, common for those with higher education, has a positive impact on cortical thickness and lowers the risk of developing Alzeihmer’s disease. Moreover, education comes with better neuronal tolerance for accumulated proteins, yet few studies take notice of more dynamic progress of the disease among adults with higher education. Summary: Research has confirmed the impact of education on cortical volume and thickness. The risk and progress of Alzheimer’s disease are also reflected in the patient’s level of education nevertheless the literature is ambiguous regarding this issue.